Fatty Acids of Densely Packed Embryos of Carcinus maenas Reveal Homogeneous Maternal Provisioning and No Within-Brood Variation at Hatching - Rey, Felisa (2020)
Embryonic development of decapod crustaceans relies on yolk reserves supplied to offspring through maternal provisioning. Unequal partitioning of nutritional reserves during oogenesis, as well as fluctuating environmental conditions during incubation, can be sources of within-brood variability. Ultimately, this potential variability may promote the occurrence of newly hatched larvae with differing yolk reserves and an unequal ability to endure starvation and/or suboptimal feeding during their early pelagic life. The present study evaluated maternal provisioning by analyzing fatty acid (FA) profiles in newly extruded embryos of Carcinus maenas Also assessed were the dynamics of such provisioning during embryogenesis, such as embryo location within the regions of the brooding chamber (left external, left internal, right external, and right internal). The FA profiles surveyed revealed a uniform transfer of maternal reserves from the female to the entire mass of embryos, and homogeneous embryonic development within the brooding chamber. Although C. maenas produces a densely packed mass of embryos that are unevenly distributed within its brooding chamber, this factor is not a source of within-brood variability during incubation. This finding contrasts with data already recorded for larger-sized brachyuran crabs, and suggests that the maternal behavior of C. maenas promotes homogeneous lipid catabolism during embryogenesis.